The Oxford companion to the Second World War - Dear, Ian 1935- (Oxford Univ. Press, 1995)
Despite Korea, despite Vietnam, despite a dozen smaller conflicts, a generation of Americans refers to World War II simply as "the War." Indeed, there has been nothing like it in human history: a single war that spanned three continents - a war which saw more men and women under arms, more deaths, and more destruction than any other. Now Oxford University Press provides the definitive one-volume reference to this cataclysmic event